(untitled) (Ustozlar uchun, 2026)
The study involved 20 patients (aged 35 to 55 years) diagnosed with Stage I–II generalized periodontitis in the remission phase. All patients underwent selective tooth grinding during the supportive therapy phase. The examination protocol included: